Animal Welfare, Moral Consumers and the Optimal Regulation of Animal Food Production - Thomas Eichner; Marco Runkel (Center for Economic Studies and ifo Institute (CESifo), 2022)
Within a general equilibrium model, this paper identifies a novel animal welfare externality that occurs if the private animal friendliness in a market economy falls short of the social animal friendliness used by the social planner when determining the efficient allocation. The animal welfare externality causes an inefficiently high quantity and an inefficiently low quality of animal food. Correction of this market failure is attained by taxing animal food output and subsidizing animal food quality. With consumer and producer heterogeneity, regulation is the same but sector-specific, with a more intense regulation in the sector with the worse living conditions of animals.
Keywords: D62; H20; Q18; 330; animal welfare; altruism; morality; non-anthropocentrism; meat tax; subsidy on animal food quality